The Long-Term Impact of the COVID-19 Pandemic on Loneliness in People Living With Disability and Visual Impairment - Heinze, Nikki; Hussain, Syeda F.; Castle, Claire L.; Godier-McBard, Lauren R.; Kempapidis, Theofilos; Gomes, Renata S. M. (Frontiers in Public Health, 2021)
Background: There has been growing concern about the impact of restrictions put in place to contain the coronavirus pandemic on loneliness, particularly in individuals with disabilities. This study explored the longitudinal impact of the pandemic on loneliness in these individuals, with a focus on those living with visual impairment (VI). Methods: An online survey was conducted in April-2020 and repeated in March 2021 to explore current life circumstances, health-related behaviours, sleep (Pittsburgh Sleep Quality Index) and social well-being, including state anxiety (State-Trait Anxiety Index) and loneliness (UCLA Loneliness scale). A convenience sample of 602 participants completed the first survey. Participants who agreed to be re-contacted were invited to take part in the follow-up survey. Results: Data is presented for the 160 participants who completed both timepoints. At both timepoints, median loneliness was significantly higher in participants with disabilities and those with VI than in participants with no disabilities. While there was no significant change in loneliness in any of the three subgroups, participants with VI experienced the largest increase in median loneliness. Loneliness was associated with having a mental health condition and higher levels of state anxiety at both timepoints. Conclusions: Individuals with disabilities such as VI experienced consistently higher levels of loneliness than those with no disabilities throughout the pandemic. While loneliness remained relatively stable in individuals with no disabilities, it increased, albeit to a non-significant level, in those with disabilities and particularly those with VI. Interventions designed to alleviate loneliness may benefit from addressing state anxiety.